Deteriorated clinical outcome in coronary artery disease patients with a high prevalence of Porphyromonas gingivalis infection. (June 2016) - Tezuka, Daisuke; Suzuki, Jun-ichi; Kosuge, Hisanori; Aoyama, Norio; Izumi, Yuichi; Yoshikawa, Shunji; Maejima, Yasuhiro; Ashikaga, Takashi; Hirao, Kenzo; Isobe, Mitsuaki
Abstract: Background: Porphyromonas gingivalis ( P. gingivalis ) is known as the main pathogen to progress periodontitis. The aim of this study was to clarify oral infection P. gingivalis in patients with coronary computed tomography angiography (CTA) diagnoses. Methods: The subjects were 50 consecutive patients who were examined by coronary CTA. Their saliva was examined for the presence of P. gingivalis by 16S rRNA-based polymerase chain reaction. The subjects were divided into 3 groups: normal coronary artery (group NC), patients with coronary plaque but without history of acute coronary syndrome (ACS) (group CP), and post-ACS (group pACS) according to their findings on CT and medical history. We assessed coronary risk factors and C-reactive protein (CRP) levels. Their medical records for the last 5 years were analyzed. Results: P. gingivalis infection was observed in 37.5% NC (N = 16), 65.2% of the CP (N = 23), and 90.9% of the pACS patients (N = 11). CRP levels in patients with P. gingivalis infection were higher than in those without the infection (0.22 ± 0.30 vs 0.07 ± 0.10 mg/dL; p = 0.031). Multiple regression analysis revealed that P. gingivalis (p = 0.047) was statistically correlated with coronary artery disease (CAD), as well as other coronary risk factors. The patients with a P. gingivalis infection exhibited lower event free survival ratio (p = 0.0348). Conclusions: P. gingivalis was identified by sensitive detection in patients with CAD, diagnosed by coronary CTA. P. gingivalis in oral saliva can be a potential marker which is associated with clinical outcomes in patients with CAD.